Enhancing Transmission Capacity of a Cognitive Radio Network by Joint Spatial-Temporal Sensing with Cooperative Communication Strategy (Global Journal of Computer Science and Technology, 2013)
In static cognitive radio network a secondary transmitter communicates directly with a secondary receiver only when the spectrum is not occupied by any primary user. The secondary user has to stop its transmission when no spectrum holes exist. To improve the transmission capacity, in this paper we approach to combine cognitive radio network with cooperative communication strategy employing spatial sensing as well as temporal sensing. In our proposed scheme when primary user is active, a secondary user transmits to another secondary user via a relay channel. By enabling the use of both the direct and relay channels, the transmission performance of the secondary system can be improved significantly. Our information-theoretic analysis as well as numerical results show that the proposed scheme significantly reduces the average symbol error probability compared to schemes based on pure temporal or spatial sensing.
Keywords: cognitive radio network; cooperative communication; joint spatial-temporal sensing; spectrum sensing; spectrum sharing